Energy cooperatives in southern European countries: Are they relevant for sustainability targets? - Susana Soeiro; Marta Ferreira Dias (Energy Reports, 2020)
The transition to low-carbon energy is a reality in Europe and most countries are on track to achieve their 2020 targets. However, there is a debate about the role of each stakeholder in this process and which of the parties most contribute. Our research focus is the role of energy cooperatives as contributors to sustainability targets, namely to energy transition, based on a database of cooperatives in southern European countries. The aim is also to compare the results with prior results on the literature. Our paper aims at answering the following questions: Are energy cooperatives important actors in the energy transition for southern European countries? Is this role different from the role of energy cooperatives in northern countries? The answer to these questions may be a starting point for discussion of different regulations and different behaviours of energy cooperatives throughout Europe and draw attention to the best way of supporting energy cooperatives. Differently, from the northern countries, the appearance of RE co-ops in Southern countries might be due to the dissatisfaction of citizens and consumer with the energy model, characterized by the dominance of the electric companies on the energy market for electric power.
Keywords: 330; Sustainability; Renewable energy; Energy cooperatives; Energy transition